Venture Capital Policy Review Spain - Tejada, Ricardo (OECD Publishing, 2003)
Spain's expanding venture capital market is still biased towards mature firms in traditional sectors with little investment in technology-based start-ups. Although the country has benefited from substantial inflows of foreign venture capital, steps are needed to increase domestic levels of entrepreneurship and risk investment expertise. The government maintains a number of small firms participatory loan schemes, which could be transformed into privately-managed equity programmes to attract venture investors. Restrictions relating to authorised venture investors and amounts could also be lightened. This paper analyses trends in Spanish venture capital markets and makes policy recommendations which have been developed through an OECD peer review process ...
Keywords: Science and Technology; Spain